Prototype of Automatic Tractor Control Navigation System Using ESP 32 Microcontroller - Abu Ammar; Muhammad Yusril; Prasepvianto Estu Broto (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
A prototype of an automatic tractor control navigation system using a microcontroller has been designed. This study aims to design a prototype of a tractor control navigation system automatically. The design begins with initializing ESP 32, followed by reading GPS (Ublox Neo M8N) and compass (QMC5883L). After that, waiting for commands from the wifi network, followed by reading waypoints, moving the motor, then the motor will drive the tractor prototype. The tests carried out included GPS and compass testing, control response testing, and waypoint navigation testing. The test results show that the accuracy of the coordinates of the GPS UBlox Neo M8N is 0.04 m from the Android smartphone GPS, the QMC5883L compass test shows the difference between the analog compass and the android smartphone compass by 0.4 degrees and 1.0 degrees. Testing the navigation system using the waypoint method, it was found that it was able to map an area or location with a distance of less than 5 meters in following the waypoint route and provide accurate coordinate information to the server during the trip as a source of map information.